Evaluation of the quality of guidelines for assisted reproductive technology using the RIGHT checklist: A cross-sectional study. (October 2019) - Xiao, Yujie; Jiang, Li; Tong, Yajing; Luo, Xufei; He, Jianghua; Liu, Lian; Gong, Chao; Ke, Lixin; Yang, Liu; Zhou, Qi; Estill, Janne; Shen, Huan; et al.
Abstract: Introduction: In recent years, assisted reproductive technology (ART) has developed rapidly, leading to an increasing number of clinical practice guidelines in this field. However, the reporting quality of current clinical practice guidelines in ART is still unknown. Objective To evaluate the reporting quality of clinical practice guidelines in the field of ART using the RIGHT checklist. Method: Relevant guidelines were identified by electronic search of PubMed, Chinese Biomedical Literature Database (CBM), Wan Fang Database and Chinese National Knowledge Infrastructure (CNKI) from the beginning of the database to October, 2017. We also searched the websites of the guideline development organizations, including Guidelines International Network (GIN), National Guideline Clearinghouse (NGC) and the National Institute for Health and Care Excellence (NICE), as well as from two medical associations, including the European Society of Human Reproduction and Embryology (ESHRE) and the American Society for Reproductive Medicine (ASRM). We used Google Scholar to find additional clinical practice guidelines (CPGs) as well. Two investigators searched the database, selected guidelines independently based on the inclusion criteria, and extracted the relevant information. Result: Fifteen guidelines (i.e. six developed by individual institutions and 9 by associations) were included. On average, 12.7 out of 35 items in the RIGHT standard (36.3%) were reported in each guideline. Five items were not reported by any of these guidelines. The reporting proportion of the seven domains (i.e. Basic information; Background; Evidence; Recommendations; Review and quality assurance; Funding and declaration and management of interests; Other information ) were 46.7%, 40.8%, 45.3%, 29.5%, 53.3%, 10.0%, 26.7%, respectively. Conclusion: At present, the reporting quality of guidelines for ART is poor, especially regarding the funding. In the future guideline development, more consideration should be given to reporting, dissemination and implementation.